Trombe wall and glazings facades: energy efficiency for different Portuguese climates - Sacht, Helenice Maria (2013)
High performance glass and Trombe walls in the façade was studied in this research. The paper reports results of an ongoing investigation on a new façade system concept, designed as: “Façade Modules for Eco-Ef! cient Refurbishment of Buildings”, especially on energy ef! - ciency of Trombe wall and glazing modules arrangement. Computational simulation was carried out by using the software DesignBuilder. Two double glazing types and Trombe walls were considered for three different climates in Portugal and four solar orientations. Results obtained for heating energy needs were compared to all façade con! gurations. The use of Trombe wall and the double self-cleaning glass in the façade point towards a signi! cant decrease of heating energy needs. The great majority of the façades combinations presented energy needs lower than the maximum allowed by the Portuguese regulation (RCCTE).